Secretory molecules from secretion systems fine-tune the host-beneficial bacteria (PGPRs) interaction - Gupta, Garima; Chauhan, Puneet Singh; Jha, Prabhat Nath; Verma, Rakesh Kumar; Singh, Sachidanand; Yadav, Virendra Kumar; Sahoo, Dipak Kumar; Patel, Ashish (Frontiers in Microbiology, 2024)
Numerous bacterial species associate with plants through commensal, mutualistic, or parasitic association, affecting host physiology and health. The mechanism for such association is intricate and involves the secretion of multiple biochemical substances through a dedicated protein system called the secretion system (SS). Eleven SS pathways deliver protein factors and enzymes in their immediate environment or host cells, as well as competing microbial cells in a contact-dependent or independent fashion. These SS are instrumental in competition, initiation of infection, colonization, and establishment of association (positive or negative) with host organisms. The role of SS in infection and pathogenesis has been demonstrated for several phytopathogens, including Agrobacterium, Xanthomonas, Ralstonia, Pseudomonas, etc. Since there is overlap in mechanisms of establishing association with host plants, several studies investigated the role of SS in the interaction of plant and beneficial bacteria, including symbiotic rhizobia and plant growth bacteria (PGPB). Therefore, the present review updates the role of different SS required for the colonization of beneficial bacteria such as rhizobia, Burkholderia, Pseudomonas, Herbaspirillum, etc., on or inside plants, which can lead to a long-term association. Most secretion systems like T3SS, T4SS, T5SS, and T6SS are required for the antagonistic activity to prevent competing microbes, including phytopathogens, and ameliorate biotic stress in plants and produce substances for successful colonization. Others are required for chemotaxis, adherence, niche formation, and suppression of immune response to establish mutualistic association with host plants.